2003
DOI: 10.1890/02-5005
|View full text |Cite
|
Sign up to set email alerts
|

Net Impact of a Plant Invasion on Nitrogen-Cycling Processes Within a Brackish Tidal Marsh

Abstract: Using comparative analysis of the rates of key processes, we have documented the net effect of a shift in plant species composition on nitrogen cycles with the example of the rapid expansion of Phragmites australis (common reed) and its replacement of short grasses (e.g., Spartina patens) in coastal marshes of the eastern United States. In this study, we measured nitrogen (N) uptake by marsh plants, N adsorption from the water column by litter, changes in N content of litter, sediment N mineralization, nitrifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(111 citation statements)
references
References 58 publications
6
104
0
1
Order By: Relevance
“…The mean concentrations of tissue nutrients of P. australis in Quebec were: N, 12.330; P, 1.515; K, 13.920; Na, 0.710; Ca, 2.780; Mg, 0.670; Cu, 0.003; Fe, 0.171; Mn, 0.125; Zn, 0.112 mg g -1 (Auclair 1979). The nitrogen concentration in aboveground tissues in August was 0.92 ± 0.12% (mean ± 2 SE) in P. australis stands in brackish tidal marshes in New Jersey, USA (Windham and Ehrenfeld 2003). Key nutrients such as N, P, and K fluctuated seasonally as well.…”
Section: Growth and Developmentmentioning
confidence: 99%
“…The mean concentrations of tissue nutrients of P. australis in Quebec were: N, 12.330; P, 1.515; K, 13.920; Na, 0.710; Ca, 2.780; Mg, 0.670; Cu, 0.003; Fe, 0.171; Mn, 0.125; Zn, 0.112 mg g -1 (Auclair 1979). The nitrogen concentration in aboveground tissues in August was 0.92 ± 0.12% (mean ± 2 SE) in P. australis stands in brackish tidal marshes in New Jersey, USA (Windham and Ehrenfeld 2003). Key nutrients such as N, P, and K fluctuated seasonally as well.…”
Section: Growth and Developmentmentioning
confidence: 99%
“…In addition, these plants could take up significantly more N (both DON and DIN) than S. alterniflora, which is evidenced by our field experiment and greater N assimilation by introduced Phragmites. Numerous studies have shown that Phragmites demands in introduced Phragmites and S. alterniflora marsh zones Estuaries and Coasts (2010) 33:784-797>50% more N than the species it displaces in salt, brackish, and tidal fresh marshes (Templer et al 1998, Windham 2001, Windham and Ehrenfeld 2003, Windham and Meyerson 2003. The high affinity and greater uptake of N could reduce N availability in sediment porewater for the other species.…”
Section: Don Assimilationmentioning
confidence: 99%
“…Over the past century, the common reed, Phragmites australis, (hereafter Phragmites) has become pervasive in Atlantic coast tidal marshes, displacing Spartina spp. and other intertidal species; its unprecedented expansion is a concern for wetland ecologists working in both tidal and non-tidal wetlands due to changes in faunal use (Meyerson et al 2000a, Angradi et al 2001, Buchsbaum et al 2006, biogeochemical cycles (Windham and Lathrop 1999, Meyerson et al 2000b, Windham and Ehrenfeld 2003, and reductions in species richness and biodiversity (Chambers et al 1999, Bertness et al 2002. Phragmites is thought to be one of the world's most widely distributed angiosperms (Holm et al 1977, Mal andNarine 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under elevated levels of CO 2 , the C 3 pathway will probably become dominant in Phragmites, and this would allow the plant to dominate the coastal salt marsh ecosystem, especially if the ecosystem experiences nitrogen enrichment through runoff [109]. If Phragmites displaces Spartina as the dominant species in the coastal marsh landscape, there might be far-reaching ecological consequences such as changes in plant species abundance [110] and trophic interactions [111,112], herbivore population crashes [113], and changes in soil biogeochemistry [114]. In this research, we don't claim that such a phenomenon is already underway, as it is beyond the scope of this study, but supporting evidence from our analysis suggests that there is a risk of such a cascading effect in future.…”
Section: Mann-kendall Trend Analysismentioning
confidence: 99%